Fresno City Council Swearing In Karen Humphrey Mayor and Council Members - Watkins, Howard::::::::: (1989)
Out-going Mayor Dale Doig presents a plaque to Incoming Mayor Karen Humphrey Plaque includes an engraved gavel and tapping block